Frequency of high– risk behaviors in health care of kashan Shahid Beheshti hospital personnel - HR Saberi; R Nabi Meibodi; M Joda Khani (طب کار)
Introduction: This study evaluated the frequency of high- risk behaviors in health care of Shahid Beheshti hospital personnel which is the largest teaching hospital of Kashan University of Medical Sciences. Methods: This was a cross- sectional, descriptive study. Health affairs including blood sampling, dressing and injections performed by medical personnel in different parts of Shahid Beheshti hospital of Kashan was assessed. Some cases of dressings, injections and blood sampling activities by health care workers, nurses and interns, were randomly selected and assessed by direct observation patients and HCWs were blinded to the study in different parts of the hospital. Results: In this study a total of 140 subjects from different parts of the hospital in the field of injections, dressings and blood sampling were evaluated. Results showed that most high- risk behaviors were related to the lack of washing hands before starting work and the least risky behavior was in appropriate way of pouring blood into the tube, not wearing gloves and not putting tourniquet 5-6 inches above the injection site in blood sampling, dressing and injection, respectively. Conclusion: It seems that one of the causes of risky behaviors in medical practices is lack of awareness among nurses and absence or lack of training programs on infection control and existing standards to control the incidence of medical personnel errors we can reduce or eliminate these errors by adequate management. Proper and regular training programs could also raise the level of personnel information and reduce the occurrence of these errors.